RAGAM BAHASA LISAN PENJUAL DAN PEMBELI DI PASAR RUBARU, KECAMATAN RUBARU, KABUPATEN SUMENEP KAJIAN SOSIOLINGUISTIK - Moh. Tarojjil Mahbub (Translation and Linguistics (Transling), 2024)
This study aims to examine oral conversations between sellers and buyers in Rubaru market, known for its linguistic diversity. The main focus is to describe the language variations used by both parties as well as the influencing factors. By employing a sociolinguistic approach and qualitative descriptive method, this research aims to present an overview of the social phenomena emerging from the conversation data. The data collection process involves direct observation at the market, recording conversations, and detailed note-taking. Through observing buying and selling transactions, conversations are recorded, transcribed, and then data is classified and grouped. The research focuses on the use of Madura language by both parties in transactions. The research findings encompass a variety of conversations between sellers and buyers in Rubaru market, showing oral language variations based on sociolect, including acrolect and basilect. Factors such as age, time, location, and gender are also found to influence the language variations used by sellers and buyers in these conversations.